A comparison of antibiotic-sterilized, stent-mounted pulmonary and aortic valve allografts in the mitral region of dogs. Issue 3 (May 1974) - Monro, J. L.; Gavin, J. B.; Barratt-Boyes, B. G.
Abstract : Monro, J. L., Gavin, J. B., and Barratt-Boyes, B. G. (1974). Thorax, 29, 323-328. A comparison of antibiotic-sterilized, stent-mounted pulmonary and aortic valve allografts in the mitral region of dogs. The mitral valves of 40 dogs were replaced with antibiotic-sterilized, stent-mounted semilunar valve allografts. Twenty grafts were pulmonary valves and 20 were aortic valves. Six dogs in each group died from causes related to the operation. All remaining dogs with pulmonary valve grafts died of causes related to the allograft itself (vegetative endocarditis (5), peripheral leak (1), cusp rupture (4), cusp shrinkage (4)). In the aortic valve group there were seven deaths from allograft endocarditis and one from a peripheral leak, but six dogs had competent allografts when sacrificed up to 12 months after surgery. It is concluded that the inherent strength and bulk of the aortic valve cusps make this valve a more suitable mitral valve replacement than the more delicate pulmonary valves.